Levels of digestible lysine for free-range chicken of the Caneludo Catolé from 1 to 105 days of age (Research, Society and Development, 2020)
Determine levels of digestible lysine for free-range chicken of the Caneludo Catolé, during the initial, growth and termination  phases. Were used150 male and female poultry in confinement cages. The digestible lysine levels used per phase: initial (1-30 dias) 0.856, 0.978, 1.100, 1.223, 1.345%, growth (30-75 dias) 0.705, 0.806, 0.906, 1.007, 1.108% and  termination (75-105 dias)  0.624, 0.713, 0.802, 0.891, 0.980%. Five treatments, three replicates, 10 chickens per experimental unit, distributed in a completely randomized design. Parameters of zootechnical evaluated: feed intake, weight gain, feed conversion ratio. The carcass characteristics evaluated: carcass, breast, drumstick, thigh, wing, neck, back, foot, gizzard, liver and heart yields. Meat quality evaluated: pH, shear force (kgf/g), cooking weight loss (%).The levels of digestible lysine influence in the initial phase with quadratic effect (P